A parallel middleware framework for vehicular network applications. (2016) - Jiang, Jianchun; Wang, Kailong; Jing, Yanmei
More and more multicore processors are applied to vehicle information terminal (VIT). It has made a great challenge to vehicular network application (VNA) development that all VNA software must be adapted to the hardware features. We propose a parallel middleware framework for VNAs in this article. Our targets aim at resolving the requirements of VNAs for real-time performance, extensibility, reusable structure and parallelisation access, and the adaptability for heterogeneous network. We discuss and present a middleware framework with multi-layer architecture, which consist of static and active modules, to be responsible for data process and message transmission respectively. Finally, we develop the middleware prototypes to verify the feasibility of our middleware framework in Linux and Android systems, and the experimental results are presented to show the value and potential of the proposed method.